2020
DOI: 10.48550/arxiv.2009.13442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the profinite rigidity of lattices in higher rank Lie groups

Abstract: We study the existence of lattices in a higher rank simple Lie group which are profinitely but not abstractly commensurable. We show that no such examples exist for the complex forms of type E 8 , F 4 , and G 2 . In contrast, there are arbitrarily many such examples for all other higher rank Lie groups, except possibly SL 2n+1 (R), SL 2n+1 (C), SL n (H), and any form of type E 6 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A special case of this theorem has geometrical relevance. It was no coincidence that all examples of profinitely commensurable but noncommensurable lattices that we constructed in [9] were cocompact.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A special case of this theorem has geometrical relevance. It was no coincidence that all examples of profinitely commensurable but noncommensurable lattices that we constructed in [9] were cocompact.…”
Section: Introductionmentioning
confidence: 99%
“…p. 15. In [9], we recently showed that for most (but not all) groups G, profinite commensurability is a strictly weaker equivalence relation on the set of lattices than commensurability. So the problem suggests itself to find the profinite commensurability classification of lattices in terms of G-arithmetic pairs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent breakthroughs are Yi Liu's result [10] that for G = PSL 2 (C), only finitely many lattices Γ ≤ G can have the same profinite completion and M. Stover's negative answer [25] for G = SU(n, 1). For most higher rank Lie groups G, the question can be answered in the negative by means of the congruence subgroup property (CSP) as we recalled in [7,Theorem 1.3]. These non-isomorphic but profinitely isomorphic lattices are however commensurable and hence not genuinely distinct.…”
Section: Introductionmentioning
confidence: 99%